USING VIDEOTAPING HOMEWORK TO IMPROVE SPEAKING ABILITY - Yella Dezas Perdani (Universitas Lambung Mangkurat, 2020)
Improving learners’ speaking ability is the main purpose of Conversation 1 Class in Tadris Bahasa Inggris STAI Bandung. One of the strategies that were given is homework. The homework was in the form of video, which was called videotaping homework. The videos contained conversations using English expressions learned in the form of roleplay. The research design was qualitative research and the data collection was questionnaire. The result showed that 75% of the learners though that this strategies was able to improve their speaking ability in terms of Productivity, Purposefulness, Challenge, Authenticity, Academically. In addition videotaping homework had academicals purpose also that it could improve speaking ability of the learners, especially English expression knowledge by re-watching the video and finding the lackness through those videos.